Pengaruh Diskon dan Promosi Terhadap Loyatitas Pelanggan di Alfamart Mega Regency 4 - Simangunsong, Chintia Novita Br; Wulandari, Gita Mei; Asriah, Nida (Innovative: Journal Of Social Science Research, 2025)
This study aims to analyze the effect of discounts and promotions on customer loyalty at Alfamart. Using a qualitative approach, this research uncovers customers' perceptions, experiences and responses to the discount and promotion strategies implemented. Data was collected through in-depth interviews with ten regular Alfamart customers in the Mega Regency area. The results show that discounts and promotions have a significant impact on customer loyalty, especially when they are relevant to customer needs. This study provides recommendations for improving the effectiveness of promotional programs.